Analysis of methodologies applied to risk management in software development projects in Colombia - Arias Murcia, Paola Andrea; Ferro Escobar, Roberto; Abuchar Porras, Alexandra (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
Risk Management is a very important factor that must be addressed from the beginning of any type of project, this is one of the fundamental aspects that allows us to see from different points of view different variables that can bring multiple problems in the execution of the project, This article emphasizes the realization of software projects due to the importance they have had in recent years and due to the high failure rates in their realization. This research considers in its methodological phase the use of Risk Management proposed by the PMBOK, the PHVA cycle and the methodology of Analysis and Risk Management of Information Systems, the use of these methodologies will allow the use and application of Proposed best practices to define threats, risks, vulnerabilities and in the future will lay the groundwork for formulating policies for continuous improvement and thus prevent these projects from failing.